Study on the Imaging Interference of a Vortex-Light-Modulated Gaussian Beam - Liu, Yanghe; Tang, Yuanhe; Zhou, Jian; Li, Cunxia; Hui, Ningju; Zhang, Yishan; Wang, Yanlong (Photonics, 2024)
Combined with vortex light and airglow, some different physical phenomena are presented in this paper. Based on the ground-based airglow imaging interferometer (GBAII) made by our group, a liquid crystal on silicon (LCoS) device on one arm of a wide-angle Michelson interferometer (MI) of the GBAII is replaced by the reflector mirror to become the GBAII-LCoS system. LCoS generates a vortex phase to convert a Gaussian profile airglow into a vortex light pattern. After the Gaussian profile vortex light equation is obtained by combining the Gaussian profile airglow with the Laguerre–Gauss light, three different physical phenomena are obtained: the simulated Gaussian vortex airglow beam exhibits a hollow phenomenon with the introduction of the vortex phase, and as the topological charge (TC) l increases, the hollow range also increases; after adding the vortex factor, the interference fringe intensity can be ‘broadened’ with the optical path difference (OPD) and TC l increases, which match the field broadening technology for solid wide-angle MI; the ‘Four-point algorithm’ wind measurement for the upper atmosphere based on the vortex airglow is derived, which is different from the usual expressions. Some experimental results are presented: We obtained the influence modes of vortex light interference and a polarization angle from 335° to 245°. We also obtained a series of interference images that verifies the rotation of the vortex light, onto which is loaded a set of superimposed vortex phase images with TC l = 3 into LCoS in turn, and the interference image is rotated under the condition of the polarization angle of 245°. The controlled vortex interference image for different TC and grayscale values are completed.